The influence of sowing dates and plant density on the yield of corn hybrids in the conditions of the Left Bank Forest-Steppe - Hanhur, V.; Pelykh, M. (Scientific Progress & Innovations, 2025)
Maize is one of the most important crops and one of the three most important grains in the world. Ensuring stable yields of this crop is a priority for modern farmers, as it is used as animal feed, raw material for the food industry, and a source of energy for bioethanol production. Therefore, the development of individual agronomic practices for each hybrid is of particular importance. The aim of the research was to determine the effect of different sowing dates and plant density on the formation of productivity of mid-season corn hybrids. Studies have shown that, on average, according to variants of different seeding rates, the maize hybrid DKS 3969 formed a maximum weight of 1000 seeds at the second sowing date, respectively 230.3 g. It was noted that early and late sowing dates led to a decrease in the above indicator, respectively, by 8.3 g and 9.9 g or 3.6 and 4.3 %. The weight of 1000 seeds of hybrids SI Ozone and P 9127 was almost the same at both the first and second sowing dates. The research has shown a significant effect of the sowing rate on the weight of 1000 seeds of corn hybrids. The maximum value of this indicator (225.6–238.4 g) was formed at the lowest seeding rate (35 thousand/ha). In the experiment was found that the maximum level of grain productivity, at all sowing dates, was formed by the hybrid P 9127 (6.40–7.84 t/ha). The yields of hybrids SI Ozone and DKS 3969 were lower than the best, respectively, by 0.07–0.13 and 0.16–0.30 t/ha or 0.9–2.0 and 2.1–4.7 %. As for the effect of seeding rates on the yield of corn hybrids, during the first sowing period, a gradual increase was observed from the lowest to the highest seeding rate. In the middle term, a significant increase in yield was observed only up to the norm of 55 thousand units/ha. At the same time, the third-term sowing of corn hybrids did not show a significant effect of sowing rates on grain yield. The difference between the variants of the experiment, according to the hybrids studied, was within the limits of the smallest significant difference. Thus, according to the results of two years of research (2023–2024), it was found that in the conditions of the Left-Bank Forest-Steppe, the most appropriate period for sowing corn is April 20–30 at a sowing rate of 65 thousand germinating seeds per hectare.